Application of Learning at Kindergarten Aisyiyah 2 During the Covid 19 Pandemic - Lia Novianti; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of writing this research is to find out how the implementation of learning in Kindergarten Aisyiyah 2 during the Covid 19 pandemic. The determination of learning at Kindergarten Aisyiyah 2 is very effective during this Covid19 pandemic. The research method used is by observation and portfolios of teachers and students at Kindergarten Aisyiyah 2 during the covid 19 pandemic, so that we can understand what learning applications are used during the COVID-19 pandemic. Kindergarten Aisyiyah 2 during the covid 19 pandemic uses online and offline learning, in the offline learning process every students get a turn to learn face to face with the teacher once a week. And at Kindergarten Aisyiyah 2, they strictly maintain health protocols by providing a place for washing hands, wearing masks during the learning process and maintaining a distance between students' seats while in class, each class contains 5 students.